Synthesis and characterization of reduced graphene oxide and their application in dye-sensitized solar cells - Ghann, William E.; Kang, Hyeonggon; Uddin, Jamal; Chowdhury, Farzana Aktar; Khondaker, Saiful I.; Kabir, Md Humayun; Moniruzzaman, Monir; Rahman, Mohammed M. (MDPI, 2019)
Reduced graphene oxide has certain unique qualities that make them versatile for a myriad of applications. Unlike graphene oxide, reduced graphene oxide is a conductive material and well suited for use in electrically conductive materials, such as solar cell devices. In this study, we report on the synthesis of graphene oxide as well as the fabrication and characterization of dye-sensitized solar cells with a photoanode which is an amalgam of reduced graphene oxide and titanium dioxide. The synthesized reduced graphene oxide and the corresponding photoanode were fully characterized using Ultraviolet-visible, Fourier transform infrared (FTIR), and Raman Spectrometry. The morphology of the sample was assessed using Atomic Force Microscopy, Field Emission Scanning Electron Microscopy, Transmission Electron Microscopy, and Energy Dispersive X-ray Spectroscopy. The photovoltaic characteristics were determined by photocurrent and photo-voltage measurements of the fabricated solar cells. The electrical impedances of both sets of devices were also evaluated. Overall, the solar to electric power efficiency of the device with reduced graphene oxide was observed to be higher (2.02%) than the device without the reduced graphene oxide (1.61%).
Keywords: titanium dioxide; Graphene Oxide (GO); Reduced Graphene Oxide (rGO); DSSC; FTIR; Raman; AFM; TEM